Joy in Learning: When Children Feel good and Realize They Learn - Cronqvist, Marita (Educare, 2021)
Both in research and in the Swedish curricula, positive emotions such as joy, pleasure and desire are said to stimulate learning. However, it is not clear what the meaning of joy is in relation to learning. The purpose of this phenomenological study is to gain knowledge about the essential meanings of the phenomenon joy in learning for children aged 9 and 12 years in compulsory school. The questions are as follows: What meanings constitute the phenomenon joy in learning in the current context? What implications do the findings have for teaching? The study is phenomenological and is based on interviews with or written stories by the participating children. The findings indicate how joy stimulates learning and emerges when children understand and ‘own’ their learning process. Teachers are important as ‘facilitators’ for joy in learning through being supportive and inspiring. Joy in learning during lessons is related to joy and friendship during school breaks. Teachers’ decisive importance for joy is discussed in relation to various modalities of pedagogical contact. Conclusions can be drawn that school breaks need attention from a learning perspective and that children need teacher support to understand their learning process.